Pelatihan Pengembangan Kelembagaan Kelompok Usaha Bersama (KUBE) di Kecamatan Moramo Utara - Muhammad Arsyad; Jamaluddin Hos; Bahtiar; Ambo Upe; Ratna Supiyah; Suharty Roslan; Dewi Anggraini (CV. Literasi Indonesia, 2022)
This article begins with the problem of developing strategies for increasing capacity and how to improve the knowledge and awareness of group members to increase the productivity of joint business balance. The implementation of the activity has taken place in stages, starting with lectures and open discussions with all members of the collaborative business group and field agricultural extension officers. Based on the results of the activities that have been carried out, the joint business group institutional development training, namely the application of concepts and techniques delivered in training, farmer groups cooperate in developing businesses while always following the recommendations of field agricultural extension officers assigned to each village in North Moramo district. To the village, sub-district, community, and provincial governments to always listen and pay attention to the needs in the context of developing the institutions of the joint business groups in each village, especially those in each town. And to the field agricultural extension officers to continue to establish a joint business group in increasing its institutional capacity. The main contribution to be achieved and expected in this activity is to make a positive contribution, especially in enriching the insights of the members of the joint business group and the agricultural extension officers of the field.